Lithium ion battery and electric device comprising same
By using high-nickel positive electrode active material and fluorosulfonate in electrolyte in lithium-ion batteries to form a CEI film, the problem of reduced stability and increased gas production when the battery improves energy density and power performance is solved, and the effects of high energy density, excellent power performance and low gas production are achieved.
Patent Information
- Application Number
- CN202410370839.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-03-28
AI Technical Summary
When existing lithium-ion batteries improve energy density and power performance, they can easily lead to reduced stability and increased gas production, affecting battery performance.
High nickel positive electrode active material is used and a certain concentration of fluorosulfonate is added to the electrolyte solution to form a solid electrolyte membrane (CEI) to reduce gas production and improve stability.
It realizes the high energy density and excellent power performance of lithium-ion batteries, while reducing gas production and improving battery stability.
Smart Images

Figure CN119833707A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery and an electrical device containing the same. Background Art
[0002] Secondary batteries represented by lithium-ion batteries have been widely used. In order to further meet the ever-evolving application needs, lithium-ion batteries are required to have high energy density and better power performance.
[0003] At present, there are two main solutions to increase the energy density of lithium-ion batteries: one is to use positive electrode materials with high nickel content; the other is to increase the operating voltage of lithium-ion batteries. However, both solutions will have a certain adverse effect on battery performance, such as reduced stability and easy gas production. Summary of the invention
[0004] The purpose of the present application is to provide a lithium-ion battery and an electrical device containing the same. The lithium-ion battery adopts a high-nickel positive electrode active material and has a high energy density, and also has the characteristics of good stability, low gas production, and excellent power performance.
[0005] To this end, a first aspect of the present application provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte;
[0006] Wherein, the positive electrode comprises a positive electrode active material, and the positive electrode active material is Li n Ni x Co y M z O f A g , wherein 0.8≤n≤1.2, 0.5≤x≤0.98, 0≤y≤0.5, 0≤z≤0.5, 0≤f≤2, the M element is selected from at least one of Mn, Al, Zr, Ti, V, Mg, Fe, B, and Mo, and the A element is selected from at least one of S, N, P, F, Cl, Br, and I; the specific surface area of the positive electrode active material is 0.2 to 1.8 m 2 / g;
[0007] The electrolyte contains an additive, and the additive includes fluorosulfonate; the mass percentage of the fluorosulfonate in the electrolyte is 0.005% to 0.1%.
[0008] By combining the positive electrode active material with the above-mentioned specific surface area with a certain concentration of fluorosulfonate, not only a higher energy density can be exerted, but also the gas production problem of the battery can be significantly reduced, and good power performance can be maintained. The main principle is that the positive electrode active material with a higher specific surface area can better exert the advantages of high energy density and good power performance, but it is also more likely to cause gas production problems. This application uses a positive electrode active material with a higher specific surface area and combines it with a certain concentration of fluorosulfonate as an electrolyte additive, so that LiF and LixSO can be formed on the positive electrode surface. y Solid electrolyte membrane (CEI) with carbon dioxide as the main material. This type of inorganic membrane is relatively stable and has low impedance under high temperature and high pressure conditions. It can prevent the solvent from directly contacting the positive electrode surface for oxidation, thereby significantly reducing gas production and helping to maintain good power performance.
[0009] In any embodiment, the specific surface area of the positive electrode active material is 0.4 to 1.3 m 2 / g.
[0010] By adopting the positive electrode active material with the above specific surface area, it is beneficial to further improve the gas production and battery power of the battery.
[0011] In any embodiment, the mass percentage of the fluorosulfonate in the electrolyte is 0.01% to 0.06%.
[0012] By making the proportion of fluorosulfonate within the above range, a better reaction can occur on the positive electrode surface to produce a suitable CEI film, which is beneficial to further improve the gas production and battery power of the battery.
[0013] In any embodiment, the negative electrode comprises a negative electrode active material, and the specific surface area of the negative electrode active material is 0.7 to 2.5 m 2 / g.
[0014] The specific surface area of the negative electrode active material will also have a certain impact on the battery power performance. In general, the larger the specific surface area, the more likely it is to increase the battery power due to the increased electrolyte contact area, and the easier it is to produce gas. This application optimizes the specific surface area of the negative electrode active material to the above range on the basis of improving the specific surface area of the positive electrode active material and the electrolyte composition, which can take into account the low gas production and high power performance of the negative electrode, and is conducive to further improving the battery performance.
[0015] In any embodiment, the specific surface area of the positive electrode active material is bm 2 / g, the specific surface area of the negative electrode active material is cm 2 / g; the ratio of b to c is 0.14~1.81.
[0016] The gas production of lithium-ion batteries is mainly caused by the oxidation or reduction of the solvent in the electrolyte. Some of the solvent is reduced on the negative electrode side to form SEI, in which case the gas production is small, and some of the solvent is oxidized on the positive electrode side and almost no CEI is generated, in which case the gas production is large. The b / c value can reflect the gas production of the solvent on the positive and negative electrode sides. When the ratio of b to c is within the above range, the improvement effect of the fluorosulfonate in the electrolyte additive on the battery gas production performance can be further enhanced.
[0017] In any embodiment, the ratio of b to c is 0.40 to 1.14.
[0018] When the ratio of b to c is within the above range, it is more conducive to improving the gas production performance and high power performance of the battery.
[0019] In any embodiment, the mass percentage of the fluorosulfonate in the electrolyte is a wt%, and the specific surface area of the positive electrode active material is bm 2 / g, the specific surface area of the negative electrode active material is cm 2 / g; the relationship between a, b, and c satisfies 1.75≤100a / (b / c)≤17.5.
[0020] The gas production of lithium-ion batteries is mainly caused by the oxidation or reduction of the solvent in the electrolyte. A part of the solvent is reduced to generate SEI on the negative electrode side, in which case the gas production is small, and a part of the solvent is oxidized on the positive electrode side and almost no CEI is generated, in which case the gas production is large. The b / c value can reflect the gas production of the solvent on the positive and negative electrode sides. When the b / c value is larger, it means that the specific surface area of the positive electrode active material in the battery system is larger, the positive electrode is more active, and the electrolyte is oxidized on the positive electrode side. The gas production will be greater; in this case, in order to improve the gas production on the positive electrode side, a larger amount of a is required. Conversely, when the b / c ratio is smaller, the required amount of a is relatively smaller. Therefore, it is reasonable to use the ratio of a to (b / c) to reflect the relationship between the concentration of fluorosulfonate and the specific surface area of the positive and negative electrode active materials. When the relationship between a, b, and c satisfies the above formula, it is beneficial to improve the gas production problem of the battery during use and storage.
[0021] In any embodiment, the fluorosulfonate includes at least one of lithium fluorosulfonate, sodium fluorosulfonate, and potassium fluorosulfonate.
[0022] The above-mentioned fluorosulfonates are more suitable for the electrolyte system of the lithium-ion battery of the present application and are more conducive to improving the battery performance than other fluorosulfonates.
[0023] In any embodiment, the additive further comprises difluorophosphate; the mass percentage of the difluorophosphate in the electrolyte is 0.001% to 0.1%.
[0024] Difluorophosphate can form MF and M on the surface of negative electrode active material. x PO y In addition, when the above mass percentage is adopted, it is beneficial to improve the power performance of the lithium-ion battery without worsening the gas generation of the battery cell.
[0025] In any embodiment, the mass percentage of the difluorophosphate in the electrolyte is 0.001% to 0.08%.
[0026] When the proportion of the additive difluorophosphate in the electrolyte is within the above range, it is beneficial to further improve the power performance of the battery.
[0027] A second aspect of the present application provides an electrical device, which includes the lithium-ion secondary battery described in the first aspect of the present application.
[0028] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used to illustrate the preferred embodiments and are not to be considered as limiting the present application. In the accompanying drawings:
[0030] Figure 1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0031] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0032] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0033] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0034] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0035] Figure 6 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;
[0036] Description of reference numerals:
[0037] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 lithium-ion battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0038] The exemplary embodiments of the present disclosure will be described in more detail below. It should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0039] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0040] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0041] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0042] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0043] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0044] Secondary batteries represented by lithium-ion batteries have been widely used. In order to further meet the ever-evolving application needs, lithium-ion batteries are required to have high energy density and better power performance. At present, there are two main solutions to improve the energy density of lithium-ion batteries: one is to use positive electrode materials with high nickel content; the other is to increase the operating voltage of lithium-ion batteries. However, both solutions will have certain adverse effects on battery performance, such as reduced stability and easy gas production.
[0045] After analysis, the main reasons for the adverse effects include: excessive nickel content will reduce the stability of the positive electrode material, and the unstable trivalent nickel ions will easily cause the electrolyte to oxidize and decompose at the positive electrode; on the other hand, increasing the battery charging voltage will increase the positive electrode potential, and the electrolyte will also be prone to oxidative decomposition. These two situations will cause a series of problems such as battery gas production, increased interface impedance, and thus deterioration of power performance. In addition, the solid electrolyte membrane (SEI) generated by the reduction of the electrolyte on the negative electrode surface will also partially decompose and produce gas.
[0046] To this end, the present application mainly reduces battery gas production and improves battery stability and power performance by simultaneously improving the specific surface area of the positive electrode active material and the electrolyte composition.
[0047] The solutions described in the embodiments of the present application are applicable to lithium-ion secondary batteries, battery modules using the secondary batteries, battery packs using the secondary batteries or battery modules, and electrical devices using at least one of the secondary batteries, battery modules and battery packs.
[0048] Lithium-ion secondary battery
[0049] In some embodiments, a lithium ion secondary battery is provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte;
[0050] Wherein, the positive electrode comprises a positive electrode active material, and the positive electrode active material is Li n Ni x Co y M z O f A g , wherein 0.8≤n≤1.2, 0.5≤x≤0.98, 0≤y≤0.5, 0≤z≤0.5, 0≤f≤2, the M element is selected from at least one of Mn, Al, Zr, Ti, V, Mg, Fe, B, and Mo, and the A element is selected from at least one of S, N, P, F, Cl, Br, and I; the specific surface area of the positive electrode active material is 0.2 to 1.8 m 2 / g;
[0051] The electrolyte contains an additive, and the additive includes fluorosulfonate; the mass percentage of the fluorosulfonate in the electrolyte is 0.005% to 0.1%.
[0052] When the specific surface area in the above range is used, the high nickel positive electrode active material can better exert the advantages of high energy density and good power performance, but at the same time, due to its high activity, it is easier to produce gas. Therefore, when the high nickel positive electrode active material with the above specific surface area is used in this application, an electrolyte containing a certain concentration of fluorosulfonate is also used. By using fluorosulfonate in the electrolyte, a LiF and LixSO y Solid electrolyte membrane (CEI) with fluorinated sulfonate as the main material is relatively stable and has low impedance under high temperature and high pressure conditions, which can prevent the solvent from directly contacting the positive electrode surface and oxidizing, thereby significantly reducing gas production. In addition, controlling the fluorinated sulfonate to 0.005% to 0.1wt% of the electrolyte is more conducive to sufficient film formation, significantly inhibiting gas production and maintaining battery power.
[0053] In this article, specific surface area, or BET (Brunauer, Emmett and Teller) specific surface area, refers to the total area per unit mass of a material, usually in m 2 / g. The specific surface area can be detected by the following method: the specific surface area is determined by the nitrogen adsorption method, and the test instrument model is the American Mack TriStarⅡ3020 / 3030. The test standard can refer to GB / T19587-2017 "Gas Adsorption BET Method for Determination of Specific Surface Area of Solid Materials". The specific surface area of the positive electrode active material can be controlled by the following process: the specific surface area of the positive electrode active material is related to the particle size distribution and single crystal size of the material, wherein the particle size distribution can be obtained by adjusting the following parameters: controlling the particle size distribution of the precursor and the process parameters of the ternary material finished product crushing and grading process, and the single crystal size can be obtained by adjusting the following parameters: precursor size / specific surface area, sintering temperature, and process parameters of the finished product crushing and grading process. The high nickel ternary materials with different BET specific surface areas involved in the embodiments of this application can all be obtained through commercial channels.
[0054] [Positive electrode]
[0055] The positive electrode sheet includes a positive current collector and a positive active material disposed on at least one surface of the positive current collector. As an example, the positive current collector has two surfaces opposite to each other in its thickness direction, and the positive active material layer is disposed on any one or both of the two opposite surfaces of the positive current collector.
[0056] In some embodiments, the specific surface area of the positive electrode active material is 0.4 to 1.3 m 2 / g; for example, it can be about 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, etc.
[0057] By adopting the positive electrode active material with the above specific surface area, it is beneficial to further improve the gas production and battery power of the battery.
[0058] In some embodiments, the positive electrode active material may be selected from any lithium transition metal oxide for lithium ion batteries known in the art that meets the following formula:
[0059] Li n Ni x Co y M z O f A g, where 0.8≤n≤1.2, 0.5≤x≤0.98, 0≤y≤0.5, 0≤z≤0.5,
[0060] 0≤f≤2, M element is selected from at least one of Mn, Al, Zr, Ti, V, Mg, Fe, B, and Mo, and A element is selected from at least one of S, N, P, F, Cl, Br, and I. For example, lithium nickel cobalt manganese oxide (such as LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.7 Co 0.2 Mn 0.1 O2 (also referred to as NCM 721 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. These positive electrode active materials may be used alone or in combination of two or more.
[0061] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0062] In some embodiments, the cathode material may further include a binder. For example, the binder may include one or a combination of two or more selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0063] In some embodiments, the cathode material may further include a conductive agent. For example, the conductive agent may include one or a combination of two or more selected from the group consisting of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0064] In some embodiments, the positive electrode sheet can be prepared in the following manner: the above-mentioned positive electrode materials, such as positive electrode active materials, conductive agents, binders and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0065] [Electrolyte]
[0066] The electrolyte plays a role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte includes a solvent, an electrolyte salt and an additive, and the electrolyte contains 0.005% to 0.1% by mass of a fluorine-containing sulfonate.
[0067] In some embodiments, the mass percentage (wt%) of the fluorosulfonate in the electrolyte is 0.01% to 0.06%, for example, about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, etc.
[0068] By making the proportion of fluorosulfonate within the above range, it is beneficial to further improve the gas production and battery power of the battery.
[0069] In some embodiments, the fluorosulfonate includes one or a combination of two or more of lithium fluorosulfonate, sodium fluorosulfonate, and potassium fluorosulfonate.
[0070] The above-mentioned fluorosulfonates have good compatibility with the battery system and are easy to form LiF and LixSO on the positive electrode surface. y and other substances, thereby forming a solid electrolyte membrane (CEI) with higher stability, effectively reducing gas production.
[0071] In some embodiments, the additive further comprises difluorophosphate; the mass percentage (wt%) of the difluorophosphate in the electrolyte is 0.001% to 0.1%; for example, it can be about 0.001%, 0.002%, 0.005%, 0.007%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, etc. As an example, the difluorophosphate can be selected from one of lithium difluorophosphate, sodium difluorophosphate, and potassium difluorophosphate, or a combination of two or more thereof.
[0072] Difluorophosphate can form MF and M on the surface of negative electrode active material. x PO y The low-impedance inorganic solid electrolyte layer (SEI) mainly composed of isocyanate is beneficial to improve the power performance of lithium-ion batteries without deteriorating the gas generation of the battery cell. In addition, if the addition amount is too small (for example, less than 0.01%), the film formation on the negative electrode surface is insufficient and the power improvement is not obvious. If the addition amount is too large (for example, greater than 0.1%), the viscosity of the electrolyte will be high and the power performance will be deteriorated.
[0073] In some embodiments, the mass percentage (wt%) of the difluorophosphate in the electrolyte is 0.001% to 0.08%.
[0074] When the proportion of the additive difluorophosphate in the electrolyte is within the above range, it is beneficial to further improve the power performance of the battery.
[0075] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0076] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0077] [Negative electrode]
[0078] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0079] In some embodiments, the specific surface area of the negative electrode active material is 0.7 to 2.5 m 2 / g; for example, it can be about 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, 2.5m 2 / g, etc.
[0080] The specific surface area of the negative electrode active material will also have a certain impact on the battery power performance. In general, the larger the specific surface area, the more likely it is to increase the battery power due to the increased electrolyte contact area, and the easier it is to produce gas. In the technical solution provided in this application, on the basis of improving the specific surface area of the positive electrode active material and the electrolyte composition, the specific surface area of the negative electrode active material is optimized to the above range, which can take into account the low gas production and high power performance of the negative electrode, and is conducive to further improvement of battery performance.
[0081] In some embodiments, the specific surface area of the positive electrode active material is bm 2 / g, the specific surface area of the negative electrode active material is cm 2 / g; the ratio of b to c is 0.14~1.81.
[0082] The gas production of lithium-ion batteries is mainly caused by the oxidation or reduction of the solvent in the electrolyte. Some of the solvent is reduced on the negative electrode side to form SEI, in which case the gas production is small, and some of the solvent is oxidized on the positive electrode side and almost no CEI is generated, in which case the gas production is large. The b / c value can reflect the gas production of the solvent on the positive and negative electrode sides. When the ratio of b to c is within the above range, the improvement effect of the fluorosulfonate in the electrolyte additive on the battery gas production performance can be further enhanced.
[0083] In some embodiments, the ratio of b to c is 0.40 to 1.14.
[0084] When the ratio of b to c is within the above range, it is more conducive to improving the gas production performance and high power performance of the battery.
[0085] In some embodiments, the mass percentage of the fluorosulfonate in the electrolyte is a wt %, and the specific surface area of the positive electrode active material is bm 2 / g, the specific surface area of the negative electrode active material is cm 2 / g; the relationship between a, b, and c satisfies 1.75≤100a / (b / c)≤17.5.
[0086] During the charge, discharge and storage process of lithium-ion batteries, gas production is mainly caused by the oxidation or reduction of the solvent in the electrolyte. A part of the solvent is reduced to generate SEI on the negative electrode side, in which case the gas production is small; another part of the solvent is oxidized on the positive electrode side and almost no CEI is generated, in which case the gas production is large. The b / c value can reflect the gas production of the solvent on the positive and negative electrode sides. When the b / c value is larger, it means that the specific surface area of the positive electrode active material in the battery system is larger, the positive electrode is more active, and the electrolyte is oxidized on the positive electrode side. The gas production will be greater; in this case, in order to improve the gas production on the positive electrode side, a larger amount of a is required. Conversely, when the b / c ratio is smaller, the required amount of a is relatively smaller. Therefore, it is reasonable to use the ratio of a to (b / c) to reflect the relationship between the concentration of fluorosulfonate and the specific surface area of the positive and negative electrode active materials. When the relationship between a, b, and c satisfies the above formula, it is conducive to improving the gas production problem of the battery during use and storage.
[0087] In some embodiments, the relationship between a, b, and c satisfies 1.75≤100a / (b / c)≤17.5; for example, the value of 100a / (b / c) can be approximately 1.75, 2.5, 3, 3.25, 3.5, 3.89, 4, 4.38, 4.75, 5, 5.38, 5.75, 6, 6.36, 6.75, 7, 7.5, 8, 8.25, 8.75, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.63, 16, 16.5, 17, 17.5, etc.
[0088] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0089] In some embodiments, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material can be a negative electrode active material for a battery known in the art. For example, the negative electrode active material includes one or a combination of two or more selected from the following group: natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 , Li-Al alloy. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for lithium-ion batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0090] In some embodiments, the negative electrode active material layer may further include a binder. For example, the binder may include one or a combination of two or more selected from the group consisting of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0091] In some embodiments, the negative electrode active material layer may further include a conductive agent. For example, the conductive agent may include one or a combination of two or more selected from the group consisting of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0092] In some embodiments, the negative electrode active material layer may further include other auxiliary agents, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0093] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode active material layer, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0094] [Diaphragm]
[0095] The diaphragm is arranged between the positive electrode plate and the negative electrode plate to play an isolating role. The present application has no particular restrictions on the type of diaphragm, and any known porous structure diaphragm with good chemical stability and mechanical stability can be selected. The material of the diaphragm can be selected from one or a combination of two or more of the following groups: glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without special restrictions. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions.
[0096] [Battery preparation]
[0097] The positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process, and then the electrolyte is injected after being packaged in an outer package to prepare a lithium-ion battery.
[0098] The outer packaging may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0099] The present application has no particular limitation on the shape of the lithium-ion battery, which may be cylindrical, square, or any other shape. Figure 1 A lithium-ion battery 5 having a square structure is used as an example.
[0100] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the lithium-ion battery 5 can be one or more, and those skilled in the art can choose according to specific actual needs.
[0101] Battery modules, battery packs
[0102] In some embodiments, lithium-ion batteries can be assembled into a battery module. The number of lithium-ion batteries contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0103] Figure 34 is an example of a battery module. Figure 3 In the battery module 4, the plurality of lithium-ion batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of lithium-ion batteries 5 may be fixed by fasteners.
[0104] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of lithium-ion batteries 5 are received in the receiving space.
[0105] In some embodiments, the lithium-ion batteries can also be assembled into battery packs.
[0106] In some embodiments, the battery modules 4 may also be assembled into a battery pack. The number of battery modules contained in the battery pack may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0107] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0108] Electrical devices
[0109] The present application also provides an electric device, which includes a lithium-ion battery provided in the present application. In some embodiments, the electric device includes at least one of the battery modules or battery packs provided in the present application. The lithium-ion battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0110] As the electrical device, a lithium-ion battery, a battery module or a battery pack can be selected according to its usage requirements.
[0111] Figure 6The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or a battery module can be used.
[0112] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0113] Example 1
[0114] According to the parameters in Table 1, the lithium-ion battery was prepared according to the following steps.
[0115] 1) Preparation of positive electrode
[0116] LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (its specific surface area bm 2 / g as shown in Table 1), conductive carbon black SP as a conductive agent and polyvinylidene fluoride (PVDF) as a binder are dispersed in N-methylpyrrolidone (NMP) as a solvent in a mass ratio of 97:2:1 and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and after drying, cold pressing, slitting and cutting, a positive electrode sheet is obtained.
[0117] 2) Preparation of negative electrode sheet
[0118] Graphite (with a specific surface area of cm 2 / g as shown in Table 1), conductive carbon black SP as a conductive agent and SBR as a binder are dispersed in deionized water as a solvent in a mass ratio of 97:2:1 and mixed evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; after drying, cold pressing, slitting and cutting, a negative electrode sheet is obtained.
[0119] 3) Diaphragm
[0120] A polyethylene film was used as the separator.
[0121] 4) Preparation of electrolyte
[0122] In an argon atmosphere glove box (H2O content <10ppm, O2 content <1ppm), ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed at a mass ratio of 25:70, and 1 mol / L of LiPF6 lithium salt was dissolved, and then an additive was added and stirred evenly to prepare an electrolyte. In the electrolyte, the additive is lithium fluorosulfonate, and its mass percentage of the electrolyte is awt%, as shown in Table 1.
[0123] 5) Preparation of lithium-ion batteries
[0124] After assembling the above-mentioned positive electrode plate, separator and negative electrode plate, injecting electrolyte, a soft-pack lithium-ion battery is prepared.
[0125] The following properties of the lithium-ion battery were tested.
[0126] (1) 60℃ gas production test
[0127] Repeat the gas volume test on the lithium-ion battery through the following steps, and calculate the gas production per unit volume of the lithium-ion battery.
[0128] Adjust the oven temperature to 25°C, place the prepared lithium-ion battery in the oven and let it stand for 60 minutes, charge it to 4.2V at a constant current of 0.5C, and then charge it at a constant voltage of 4.2V with a cut-off current of 0.05C (this is regarded as a full charge of the battery, 100% SOC), then let it stand for 10 minutes, discharge it to 2.8V at 0.2C, and the discharge capacity in this step is recorded as C0, and let it stand for 10 minutes. Use the same process to fully charge the battery cell (100% SOC), then let it stand for 10 minutes, remove the battery cell from the test channel and test the volume of the battery cell at this time by the drainage method, which is recorded as V0. Adjust the oven temperature to 60°C, place the battery cell with the above test volume in the oven for high-temperature storage, remove the battery cell after 3 days, and test the volume of the battery cell by the drainage method after cooling to room temperature, and record it as V n , gas production per unit volume of battery cell = (V n -V0) / C0. Repeat the above test steps and record the gas production of the battery cell at 60°C until the battery cell volume expands to 50% of the original volume.
[0129] (2) 25℃ initial DCR performance test
[0130] Perform an initial DCR test on a Li-ion battery using the following steps.
[0131] The oven temperature was adjusted to 25°C, the prepared lithium-ion battery was placed in the oven and allowed to stand for 60 minutes, charged to 4.2V at a constant current of 0.5C, and then charged at a constant voltage of 4.2V with a cut-off current of 0.05C (this was regarded as full charge of the battery, 100% SOC), then allowed to stand for 10 minutes, discharged to 2.8V at 0.2C, the discharge capacity of this step was recorded as C0, and allowed to stand for 10 minutes; then allowed to stand in a 25°C oven for 60 minutes, the lithium-ion battery was charged to 4.2V at a constant current of 0.5C, and then charged at a constant voltage of 4.2V with a cut-off current of 0.05C (100% SOC), then allowed to stand for 10 minutes, discharged at 0.5C for 60 minutes, and then allowed to stand for 60 minutes; then discharged at 4C for 60 seconds (the stepping interval was 0.1S), and the voltage and current of the battery cell before and after 4C discharge were extracted, and recorded as V t0 、Vt1 ,I t0 ,I t1 , DCR=(V t1 -V t0 ) / (I t0 -I t1 ).
[0132] The above test results are shown in Table 1.
[0133] Embodiments 2 to 6
[0134] As shown in Table 1, the preparation and testing were the same as in Example 1 except that the mass percentage (a wt %) of the fluorosulfonate in the electrolyte was different.
[0135] Embodiments 7 to 11
[0136] As shown in Table 1, except for the specific surface area of the positive electrode active material (bm 2 The preparation and testing were the same as in Example 1 except that the amount of MgCl2O3 was different.
[0137] Embodiments 12 to 14
[0138] As shown in Table 1, except for the specific surface area (cm 2 The preparation and testing were the same as in Example 1 except that the amount of MgCl2O3 was different.
[0139] Embodiment 15
[0140] The preparation and testing were carried out in the same manner as in Example 1 except that lithium fluorosulfonate was replaced by sodium fluorosulfonate. The results are shown in Table 1.
[0141] Example 16
[0142] The preparation and testing were carried out in the same manner as in Example 1 except that lithium fluorosulfonate was replaced by potassium fluorosulfonate. The results are shown in Table 1.
[0143] Examples 17 to 21
[0144] As shown in Table 1, the preparation and testing are the same as in Example 1, except that the electrolyte additive further includes lithium difluorophosphate and the mass percentage (d wt %) of lithium difluorophosphate in the electrolyte is different.
[0145] Embodiment 22
[0146] In addition to the positive electrode active material from LiNi 0.8 Co 0.1 Mn 0.1 O2 replaced by LiNi 0.6 Co 0.2 Mn 0.2 Except for O2, the preparation and testing were the same as in Example 1. The results are shown in Table 1.
[0147] Embodiment 23
[0148] In addition to the positive electrode active material from LiNi 0.8 Co 0.1 Mn 0.1 O2 replaced by LiNi 0.7 Co 0.2 Mn 0.1 Except for O2, the preparation and testing were the same as in Example 1. The results are shown in Table 1.
[0149] Embodiments 24 to 25
[0150] Except for using the parameters shown in Table 1, the preparation and testing were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0151] Comparative Examples 1-2
[0152] As shown in Table 1, except for the specific surface area of the positive electrode active material (bm 2 The preparation and testing were the same as in Example 1 except that the amount of MgCl2O3 was different.
[0153] Comparative Example 3
[0154] The preparation and testing were performed in the same manner as in Example 1 except that the electrolyte did not contain any additives. The results are shown in Table 1.
[0155] Comparative Examples 4-5
[0156] As shown in Table 1, the preparation and testing were the same as in Example 1 except that the mass percentage (a wt %) of the fluorosulfonate in the electrolyte was different.
[0157] Comparative Example 6
[0158] The preparation and testing were the same as in Example 1 except that the additive was replaced by lithium fluoride instead of lithium fluorosulfonate. The results are shown in Table 1.
[0159] Comparative Example 7
[0160] In addition to the positive electrode active material from LiNi 0.8 Co 0.1 Mn 0.1 O2 replaced by LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Except for O2, the preparation and testing were the same as in Example 1. The results are shown in Table 1.
[0161] Table 1
[0162]
[0163]
[0164] According to Table 1, by comparing the embodiments of the present application and the comparative examples, it can be seen that the technical solutions of the embodiments of the present application effectively improve the gas production and power performance of the battery.
[0165] Referring to Example 1 and Comparative Examples 1-2, when the specific surface area of the positive electrode active material in the battery system is too small (less than 0.2 m 2 / g) or too large (greater than 1.8m 2 / g), the effect of the fluorosulfonate in the electrolyte additive on improving the gas production and electric power performance of the battery is obviously insufficient.
[0166] Referring to Example 1 and Comparative Example 3, when the electrolyte does not contain fluorosulfonate, there is almost no improvement on the gas generation and electric power performance of the battery.
[0167] Referring to Example 1 and Comparative Examples 4 to 5, the content of fluorosulfonate in the electrolyte has a significant effect on whether the battery performance can be effectively improved. When its content is too low (lower than 0.005wt%), the reaction between it and the positive electrode surface is too weak to improve the gas production. When its content is too high (higher than 0.1wt%), the reaction between it and the positive electrode is strong, which has a certain negative impact on the performance of the battery, resulting in poor gas production and electric power performance.
[0168] Referring to Example 1 and Comparative Example 6, when other additives such as lithium fluoride are used in the electrolyte, there is no improvement in the gas production performance of the battery. This is mainly because lithium fluoride is relatively stable and cannot play the same function as fluorosulfonate in forming a CEI film, so there is no improvement in gas production and electric power performance.
[0169] Referring to Example 1 and Comparative Example 7, when a low-nickel positive electrode active material is used, due to its relatively weak activity, its own gas production problem is not as serious as that of a high-nickel positive electrode active material, and the effect of fluorosulfonate on improving its gas production is also weak.
[0170] From the test results of each embodiment, it can be seen that when the ratio of the specific surface area of the positive electrode active material to the negative electrode active material b / c is 0.14 to 1.81, the gas production and electric power performance of the battery can be improved. In addition, referring to Examples 7 to 14 and 24 to 25, it can be seen that when the b / c value is 0.40 to 1.14, it is beneficial to further improve the gas production and electric power performance at the same time.
[0171] From the test results of each embodiment, it can be seen that for the relationship between a, b, and c, a / (b / c) can vary within a relatively large range, and all have a certain improvement effect on battery performance. In particular, when 1.75≤100a / (b / c)≤17.5 is satisfied, the improvement effect is more obvious.
[0172] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A lithium ion secondary battery, characterized in that: Including positive electrode, negative electrode, separator and electrolyte; The positive electrode includes a positive electrode active material, and the positive electrode active material is Li n Ni x Co y M z O f A g , wherein 0.8≤n≤1.2, 0.5≤x≤0.98, 0≤y≤0.5, 0≤z≤0.5, 0≤f≤2, the M element is selected from at least one of Mn, Al, Zr, Ti, V, Mg, Fe, B, and Mo, and the A element is selected from at least one of S, N, P, F, Cl, Br, and I; the specific surface area of the positive electrode active material is 0.2 to 1.8 m 2 / g; The electrolyte contains an additive, and the additive includes fluorosulfonate; the mass percentage of the fluorosulfonate in the electrolyte is 0.005% to 0.1%.
2. The lithium ion secondary battery according to claim 1, characterized in that The specific surface area of the positive electrode active material is 0.4 to 1.3 m 2 / g.
3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The mass percentage of the fluorosulfonate in the electrolyte is 0.01% to 0.06%.
4. The lithium ion secondary battery according to any one of claims 1 to 3, wherein The negative electrode comprises a negative electrode active material, and the specific surface area of the negative electrode active material is 0.7 to 2.5 m 2 / g.
5. The lithium ion secondary battery according to claim 4, characterized in that The specific surface area of the positive electrode active material is bm 2 / g, the specific surface area of the negative electrode active material is cm 2 / g; the ratio of b to c is 0.14~1.
81.
6. The lithium ion secondary battery according to claim 5, characterized in that The ratio of b to c is 0.40 to 1.
14.
7. The lithium ion secondary battery according to claim 5 or 6, characterized in that: The mass percentage of the fluorosulfonate in the electrolyte is a wt %, and the specific surface area of the positive electrode active material is bm 2 / g, the specific surface area of the negative electrode active material is cm 2 / g; the relationship between a, b, and c satisfies 1.75≤100a / (b / c)≤17.
5.
8. The lithium ion secondary battery according to any one of claims 1 to 7, wherein The fluorosulfonate includes at least one of lithium fluorosulfonate, sodium fluorosulfonate and potassium fluorosulfonate.
9. The lithium ion secondary battery according to any one of claims 1 to 8, wherein The additive further comprises difluorophosphate; the mass percentage of the difluorophosphate in the electrolyte is 0.001% to 0.1%.
10. The lithium ion secondary battery according to claim 9, characterized in that The mass percentage of the difluorophosphate in the electrolyte is 0.001% to 0.08%.
11. An electrical device, characterized in that: The electric device comprises the lithium ion secondary battery according to any one of claims 1 to 10.
Citation Information
Patent Citations
Electrolyte and lithium ion battery
CN112736285A
Battery
CN116741929A
Electrolyte for lithium secondary battery, secondary battery, and electric device
CN117083745A
Secondary battery and electric device
CN117254118A
Lithium secondary battery and method for manufacturing the same
JP2016091724A